Direct oxidation of nitrogen on ZnFexCo2-xO4 spinel oxide in alkaline solution - Khaw, Eu Sheng (Nanyang Technological University, 2020)
Nitrate (NO3-) is an important inorganic compound due to its important role as oxidizing agent and fertilizer in agriculture. Currently, the most common procedure to obtain nitrate is via Ostwald and Haber-Bosch (H-B) process. Both two method are highly energy consuming method which both require to operate in a high-temperature and high-pressure environment. Thus, an alternate production method under ambient condition is highly desired. In this report, an alternative production method through the electrochemical nitrogen oxidation reaction (NOR) in an alkaline electrolyte which catalysed by a series of ZnFexCo2-xO4 spinel oxides is developed. In this series of ZnFexCo2-xO4 spinel oxides, the optimum catalytic performance is obtained by ZnFe0.4Co1.6O4 oxide at a applied potential of 1.6 V vs. reversible hydrogen electrode (RHE) with the nitrate production rate of 130 μmol h-1 gMO-1.This project provides an energy saving and environment friendly alternative method for the production of nitrate.